Genotoxicity evaluation of tobacco and nicotine delivery products: Part Two. In vitro micronucleus assay. (October 2019) - Thorne, David; Leverette, Robert; Breheny, Damien; Lloyd, Mel; McEnaney, Stephen; Whitwell, James; Clements, Julie; Bombick, Betsy; Gaça, Marianna
Abstract: In this study, a variety of test matrices from tobacco and nicotine delivery products were assessed against a 3R4F Kentucky reference cigarette using the in vitro micronucleus assay. Testing was conducted using two Chinese hamster cell lines (CHO and V79), and a human lymphoblastoid cell line (TK6), in accordance with established guidelines. Total particulate matter (TPM) from a 3R4F Reference cigarette was compared to an electronic cigarette e-liquid, electronic cigarette TPM and TPM from a commercial tobacco heating product using a standard and an extended treatment condition with recovery period. Cells were assessed with 3R4F TPM prior to assessment of the other tobacco and nicotine product test matrices. These cell lines gave varied responses to 3R4F TPM with the most robust response using V79 cells. The use of an extended exposure/recovery period was seen to increase assay sensitivity for CHO and V79 cell lines but was less clear for TK6 cells. Negative responses were observed for all products except 3R4F across all treatment conditions in V79 cells. The most potent response to cigarette smoke was following extended treatment with recovery, suggesting this may be a more appropriate treatment for the future assessment of tobacco and nicotine product test matrices. Highlights: Particulate matter from a cigarette was compared against a commercial e-liquid e-cigarette and commercial THP. Data were contextualised against nicotine equivalents to enable comparisons between different test matrices and products. An extended recovery period of 1.5–2 cell cycles was used to increase assay sensitivity. All cells (CHO, V79 and TK6) showed an increase in IVMNBN cells following the extended recovery period. None of the NGPs tested produced a positive response, whereas cigarette smoke was positive under all test conditions.